Correction to: Long-term impact of an invasive predator on the diversity of fish assemblages in a neotropical reservoir (Biological Invasions, (2024), 26, 4, (1255-1267), 10.1007/s10530-023-03243-9) - Orlandi Neto, Aymar [UNESP]; Caneppele, Danilo; Marques, Hugo; Dias, João Henrique Pinheiro [UNESP]; Balbuena, Juan Antonio; de Oliveira, Claudio [UNESP]; Ramos, Igor Paiva [UNESP] (Springer Nature, 2024)
The Acknowledgements section was missing from this article and should have read “The researchers also thank the 2020/00590-6, São Paulo Research Foundation (FAPESP) for the Doctoral scholarship granted to A.O.N 1st author. We are grateful to the Companhia Energética de São Paulo (CESP) for providing the dataset and information about the reservoir used in this study. We would like to thank the people from the Fish Ecology Laboratory (Pirá/UNESP). The study was financed in part by Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – Brasil (CAPES) – “Finance Code 001”, the Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq) – “Finance Code 001”.